Flood processes in Canada: Regional and special aspects - Buttle, James M.; Allen, Diana M.; Caissie, Daniel; Davison, Bruce; Hayashi, Masaki; Peters, Daniel L.; Pomeroy, John W.; Simonovic, Slobodan P.; St-Hilaire, André; Whitfield, Paul H. (2016)
This paper provides an overview of the key processes that generate floods in Canada, and a context for the other papers in this special issue – papers that provide detailed examinations of specific floods and flood-generating processes. The historical context of flooding in Canada is outlined, followed by a summary of regional aspects of floods in Canada and descriptions of the processes that generate floods in these regions, including floods generated by snowmelt, rain-on-snow and rainfall. Some flood processes that are particularly relevant, or which have been less well studied in Canada, are described: groundwater, storm surges, ice-jams and urban flooding. The issue of climate change-related trends in floods in Canada is examined, and suggested research needs regarding flood-generating processes are identified.
MAG ID: 2298325701
Keywords: Ouvrage_Collectif_Numéro1